ANALISIS PRODUK KRIMER KENTAL MANIS DALAM RANGKA PENGEMBANGAN STANDAR NASIONAL INDONESIA BARU - Reno Fitri Hasrini; Ainun Khoiriyah (JURNAL STANDARDISASI, 2018)
Currently many milk derivative products are difficult to differentiated, namely sweetened condensed milk (SCM), non dairy sweetened condensed milk (NDSC) and sweetened condensed creamer (SCC). Therefore, it is necessary to mapping the concept of quality requirements for the three products. There are no national and international standards that govern and distinguish the characteristics of the products. To find out the characteristics of local SCC in Indonesia and compare them with imported SCC, it is necessary to analyze various local and imported SCC where circulating in the market. The materials used are local SCC 10 brands and 5 brand imports. The analysis carried out was water content, protein (Nx 6.38%), total fat and sugar content as saccharose. The results of the analysis showed that the local SCC had average of water content, protein (Nx6.38%), total fat and sugar content as saccharose were 22.68 ± 2.51, 2.27 ± 0.14, 10.74 ± 0, 89, and 47.05 ± 1.25%, respectively. Whereas imported SCC had average of water content was 22.68 ± 2.68%, protein (Nx6.38%) was 1.42 ± 0.11%, total fat was 10.33 ± 0.09% and sugar content as saccharose was 50.5 ± 2.77%. Quality requirements for local and imported SCC suitable for the Indonesian National Standard Concept of sweetened condensed cremer and were not suitable with quality requirements of non dairy sweetened condensed milk concept.